GLOBALIZATION, HUMAN RIGHTS, AND THE SOCIAL DETERMINANTS OF HEALTH - Chapman, Audrey R. (Bioethics, 2009)
Globalization, a process characterized by the growing interdependence of the world's people, impacts health systems and the social determinants of health in ways that are detrimental to health equity. In a world in which there are few countervailing normative and policy approaches to the dominant neoliberal regime underpinning globalization, the human rights paradigm constitutes a widely shared foundation for challenging globalization's effects. The substantive rights enumerated in human rights instruments include the right to the highest attainable level of physical and mental health and others that are relevant to the determinants of health. The rights stipulated in these documents impose extensive legal obligations on states that have ratified these documents and confer health entitlements on their residents. Human rights norms have also inspired civil society efforts to improve access to essential medicines and medical services, particularly for HIV/AIDS. Nevertheless, many factors reduce the potential counterweight human rights might exert, including and specifically the nature of the human rights approach, weak political commitments to promoting and protecting health rights on the part of some states and their lack of institutional and economic resources to do so. Global economic markets and the relative power of global economic institutions are also shrinking national policy space. This article reviews the potential contributions and limitations of human rights to achieving greater equity in shaping the social determinants of health.